Serological survey of Toxoplactna gondii antibodies using latex agglutination test in chickens in Lampung province - Kayoko Matsumoto (Jurnal Ilmu Ternak dan Veteriner, 1996)
A serological survey of antibodies to Toxoplarma gondii using latex agglutination test (LAT) was carried out from February to March 1995 in several areas ofLampung province, Sumatra, Indonesia, with seropositivity of 2.5% in 80 layers and 6 .0% in 50 village chickens . The test results were determined positive for T. gondii infection if the antibody titres were more than 1 :64   Key words : Toxoplarma gondii, antibody, latex agglutination test, chicken, Lampung province